Secret Sharing Approach in Multi-database System - Choudhary, Shipra PraveenKumar; Katarni, Apeksha; Manjrekar, Shweta; Devmane, Mrs. Vidyullata; Hirlekar, Mrs. Vaishali (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Secret sharing schemes are ideal for storing highly sensitive data. A secret is divided into many parts and every participant gets his unique part. If we combine all of these parts and try regenerating the secret then it might be impractical, and therefore the threshold scheme is used. Shamir’s secret sharing scheme supports the same. Here, some of the parts or all of them are required to reconstruct the secret. Any threshold number of parts are sufficient to reconstruct the original secret. The Admin has a set of files which are confidentiality and availability of data. Whenever a Client requests to access the files, the Admin performs authentication of the user through an encrypted and stored on multiple databases so as to achieve Authentication module, who makes use if Shamir's secret sharing concept. This is similar to the One Time Password (OTP) mechanism. If the Client is authentic, Admin grants him the decryption key and the Client can access the file. In this paper, we shall discuss all this in detail using which we can provide security, replication of data and authentication.